UANG SASUDUIK DALAM SISTEM PERKAWINAN DI NAGARI SITUJUAH GADANG KECAMATAN SITUJUAH LIMO NAGARI KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - Annisa Umulhusni; Nur Fatoni (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2020)
ABSTRACTObligatory giving by a prospective bridegroom to a prospective bride in a marriage is only a dowry, as explained in Article 30 of the Compilation of Islamic Law. Whereas in traditional marriages in Nagari Situjuah Gadang Situjuah District Limo Nagari Lima Puluh Regency in West Sumatra Province, a man who is going to get married is not required to give dowry only but is also required to give sasuduik money. Sasuduik money is a gift that is required to be a man who will get married by giving the amount of money desired by his future wife and family. If the sasuduik money cannot be fulfilled by men, the marriage will be delayed or even canceled. The purpose of this research is to find out the marriage system; the origin and position of Sasuduik money in the marriage system; a review of Islamic law on the provision of money for men who will hold marriages in Nagari Situjuah Gadang Situjuah Limo Nagari District Lima Puluh Regency City of West Sumatra Province. Keywords: Dowry, Marriage, Uang Sasuduik